Systematic water sprinkler / Muhammad Amirul Basaruddin & Hafizul Rakiff Zulkafli - Basaruddin, Muhammad Amirul; Zulkafli, Hafizul Rakiff (2015)
The systematic water sprinkler is the first project for our final year project. This project actually chosen from us and guidance from our supervisor discussed about project idea. The main purpose of creating this water sprinkler is to design watering plant using Arduino and detect soil moisture using moisture sensor. Besides, another purpose is to display the feedback at the LCD and switch the valve and water the soil if the soil is dry in automatically. This project only to ease people that do not have enough time to water the plant. It only needed to be placed in any desired place so that the valve can automatically watering the plant. This project only water the plant that do not have enough humidity of soil.